2020
DOI: 10.5897/jdae2019.1086
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of artificial insemination service for cattle crossbreeding by smallholder farmers in Laelay-Maichew district, Tigray, Ethiopia

Abstract: Adoption of artificial insemination (AI) inEthiopia is low and there is paucity of information in documentation. Therefore, the aim of this study is to identify the determinants of smallholder farmers' adoption of AI technology in Laelay-Maichew district. Multi-stage random sampling technique was employed to select 155 sample respondents for the study. The primary data were collected through individual interviews using semi-structured interview and check list. Descriptive, inferential statistics and binary log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Walaupun Pendidikan formal peternak cukup baik namun keikutsertaan dalam program IB masih rendah. Hal ini berbeda dengan pendapat Abraha et al (2020) bahwa pengetahuan merupakan faktor penentu utama dalam adopsi metode IB untuk meningkatkan pendapatan rumah tangga. Di Kecamatan Waelata peternak cenderung mempertimbangkan terlebih dahulu program yang ditawarkan untuk diterapkan.…”
Section: Karakteristik Peternakunclassified
“…Walaupun Pendidikan formal peternak cukup baik namun keikutsertaan dalam program IB masih rendah. Hal ini berbeda dengan pendapat Abraha et al (2020) bahwa pengetahuan merupakan faktor penentu utama dalam adopsi metode IB untuk meningkatkan pendapatan rumah tangga. Di Kecamatan Waelata peternak cenderung mempertimbangkan terlebih dahulu program yang ditawarkan untuk diterapkan.…”
Section: Karakteristik Peternakunclassified
“…In such cases, alternative options were available, such as visiting the AI technician's residence directly since the area was easily accessible to the farmer. The possession of a mobile device is also a crucial determinant factor that enables AI beneficiaries to receive prompt service from the AI technician when their cows come into heat (Abraha et al, 2020). According to research conducted by Bonewati et al (2020), a minority of farmers in Soppeng Regency showed no intention of getting their cows' pregnancy checked.…”
Section: Regional Accessibilitymentioning
confidence: 99%
“…The stages of a person's decision to accept or adopt an innovation generally go through five stages, namely: awareness, interest, assessment, try and accept [13]. Furthermore, [15] stated that artificial insemination as innovation is a stimulus for farmers to respond based on the innovation itself, which has the following properties: relative advantage, conformity to circumstances (compatibility), difficulty level (complexity), can be tried on a small scale (triability), and the results can be seen (observability).…”
Section: Factors Influencing Farmers Decision To Adopt Artificial Insemination Innovationmentioning
confidence: 99%
“…Farmers' perceptions of Artificial Insemination are the responses of goat breeders to Artificial Insemination, which can be seen from the breeders' level of knowledge, interest of breeders, and beef cattle farmers' assessment of the benefits of artificial insemination as an innovation for them [13].…”
Section: Farmers' Attitudes Of Introducing Goats Artificial Inseminationmentioning
confidence: 99%